Integrating Inclusive Learning Theories and Islamic Values in Islamic Religious Education for Students with Special Needs - Azis, Abdul; Qodir , Abdul; Mazrur; Saihu , Made (Al-Mudarris, 2025)
This study examines the implementation of learning theories in Islamic Religious Education (IRE) at SLBN-1 Palangka Raya by positioning learners with special needs as dignified subjects of learning in spiritual and humanistic terms. It responds to the need for pedagogical approaches that combine instructional effectiveness with the internalization of Islamic values for learners with cognitive, motor, and communication limitations. The study aims to analyze how IRE teachers integrate modern learning theories with the principles of tarbiyah Islamiyyah within inclusive and contextual teaching practices. Using a qualitative case study design, data were collected through classroom observations, in-depth interviews with IRE teachers, and relevant documentation. The findings show that teachers employ adaptive instructional strategies, including simplified lectures, demonstrations, drills, and dialogic questioning, supported by individualized and humanistic approaches. Various visual and concrete media such as images, physical teaching aids, animated videos, and Arabic letter flashcards are utilized to enhance comprehension. These practices reflect the application of Paivio’s dual coding theory, Dale’s cone of experience, and the humanistic theories of Maslow and Rogers, while simultaneously embedding Islamic values of raḥmah (compassion), ta’dīb (moral cultivation), and tazkiyat al-nafs (spiritual purification). This study demonstrates that the integration of modern learning theories and Islamic values in inclusive IRE not only strengthens conceptual understanding but also nurtures spiritual awareness, religious motivation, and meaningful learning experiences for students with special needs.